Diagnostic and Prognostic Values of Antinuclear Immunoglobulin G in Pediatric Lupus Patients - El-Gamasy, Mohamed Abdel-Azez; Elbendary, Amal (Iranian journal of kidney diseases, 2019)
Systemic lupus erythematous (SLE) as an autoimmunedisease caused by self immunoglobulin. It was proposed thatthe chromatin including nucleosomes is the main antigen inthe pathogenesis of SLE, and that antinuclear immunoglobulinG are associated with disease activity. Aim of the study was tostudy the diagnostic and prognostic value of serum levels ofantinuclear immunoglobulin G as the most famous anti-chromatinimmunoglobulin as a diagnostic tool and a disease activity markerin juvenile systemic lupus erythematous. The work was conducted on 90 pediatric Lupuspatients who attended to the Pediatric Nephrology Unit ofPediatric Department of Tanta University Hospital. Also on thirtyapparently healthy children with matched age and sex served asa control group. All subjects were subjected to history in details,clinical examination, SLEDAI score, anti-dsDNA and antinuclearimmunoglobulin G assay . The mean serum level of antinuclear immunoglobulinG was statistically significantly higher in patients than controls(P < .001). But there was no statistically significant differencebetween patients' subgroups. There was a weak positive correlationbetween serum antinuclear immunoglobulin G and SLEDAI score(r = 0.213) but strong correlation between anti-dsDNA antibody andSLEDAI score (r = 0.711). Antinuclear immunoglobulin G showedhigher sensitivity but equal specificity to anti-dsDNA antibody forthe diagnosis of pediatric lupus patients. Antinuclear immunoglobulin G are more accurate thananti-dsDNA antibodies in the diagnosis of pediatric lupus patientsin anti-dsDNA negative children as antinuclear immunoglobulin Ghave higher sensitivity but as regard to disease activity antidsDNAantibody is more accurate.